2008
DOI: 10.1161/circulationaha.107.730069
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase Type 6 Deletion Decreases Left Ventricular Function via Impaired Calcium Handling

Abstract: Background-Adenylyl cyclases (ACs) are a family of effector molecules for G-protein-coupled receptors. The 2 ACs most abundantly expressed in cardiac myocytes are types 5 (AC5) and 6 (AC6), which have 65% amino acid homology. It has been speculated that coexpression of 2 AC types in cardiac myocytes represents redundancy, but the specific role of AC6 in cardiac physiology and its differences from AC5 remain to be defined. Methods and Results-We generated transgenic mice with targeted deletion of AC6. Deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 27 publications
8
115
0
Order By: Relevance
“…1A, lane 3), indicating that the AC5/6 antibody favorably cross-reacts with the AC6 protein alone. A recent study (27) also showed that the commercial antibody failed to detect AC5 protein in the AC6 KO hearts, further corroborating our results.…”
Section: Discussionsupporting
confidence: 92%
“…1A, lane 3), indicating that the AC5/6 antibody favorably cross-reacts with the AC6 protein alone. A recent study (27) also showed that the commercial antibody failed to detect AC5 protein in the AC6 KO hearts, further corroborating our results.…”
Section: Discussionsupporting
confidence: 92%
“…AC6 -/-mice were described previously (50), and WT littermates were used as controls. A conditional mouse model with AC6 constitutively deleted specifically in CNT cells and CD PCs (termed AC6 loxloxCre mice) was generated by breeding transgenic mice in which exons 3-12 of the Adcy6 gene were flanked by loxP sites (termed AC6 loxlox , ref.…”
Section: Methodsmentioning
confidence: 99%
“…Age-matched adult male and female AC6 2/2 and WT littermates were generated as described 53 using heterozygous breeding; their genetic background is a mix of 129Sv/J and C57BL/6. Mice were fed either a control diet (0.6% P i , 0.8% Ca 2+ ; Harlan Teklad, Madison, WI) or for studying the effect of P i intake, a zero P i diet (0% P i , 0.8% Ca 2+ ; Harlan Teklad).…”
Section: Concise Methodsmentioning
confidence: 99%